Selecting Native Arbuscular Mycorrhizal Fungi to Promote Cassava Growth and Increase Yield under Field Conditions - Séry, D. Jean-Marc; Kouadjo, Z. G. Claude; Voko, B. R. Rodrigue; Zézé, Adolphe (Frontiers in Microbiology, 2016)
The use of arbuscular mycorrhizal fungal (AMF) inoculation in sustainable agriculture is now widespread worldwide. Although the use of inoculants consisting of native AMF is highly recommended as an alternative to commercial ones, there is no strategy to allow the selection of efficient fungal species from natural communities. The objective of this study was (i) to select efficient native AMF species(ii) evaluatetheir impact on nematode and water stresses, and (iii) evaluate their impact on cassava yield, an important food security crop in tropical and subtropical regions. Firstly, native AMF communities associated with cassava rhizospheres in fields were collected from different areas and 7 AMF species were selected, based upon their ubiquity and abundance. Using these criteria, two morphotypes (LBVM01 and LBVM02) out of the seven AMF species selected were persistently dominant when cassava was used as a trap plant. LBVM01 and LBVM02 were identified as Acaulospora colombiana (most abundant) and Ambispora appendicula, respectively, after phylogenetic analyses of LSU-ITS-SSU PCR amplified products. Secondly, the potential of these two native AMF species to promote growth and enhance tolerance to root-knot nematode and water stresses of cassava (Yavo variety) was evaluated using single and dual inoculation in greenhouse conditions. Of the two AMF species, it was shown that A. colombiana significantly improved the growth of the cassava and enhanced tolerance to water stress. However, both A. colombiana and A. appendicula conferred bioprotective effects to cassava plants against the nematode Meloidogyne sp.,ranging from resistance (suppression or reduction of the nematode reproduction) or tolerance (low or no suppression in cassava growth). Thirdly, the potential of these selected native AMF to improve cassava growth and yield was evaluated under field conditions, compared to a commercial inoculant. In these conditions, the A. colombiana single inoculation and the dual inoculation significantly improved cassava yield compared to the commercial inoculants. This is the first report on native AMF species exhibiting multiple benefits for cassava crop productivity, namely improved plant growth and yield, water stress tolerance and nematode resistance.